Linear multivariable control with decoupling in a heat exchanger - Ricardo-Barrera, Jaime Freddy; Barrios-Urueña, Edgar (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2017)
This document describes the validation of linear multivariable control designs in a heat exchanger under virtual environment using Hysys, where the interest was focused on the analysis of the different responses of MIMO system when regulatory control was done with different decouplers and without decoupler. Three types of decoupling were used: Steady-State Simplified, Simplified and Generalized. The values of the set-points were 60 °C for the flow temperature at the outlet of the tubes, and 41 °C for the flow temperature at the outlet of the shell; the manipulated variables were the flows into the tubes and the shell, because percentages of opening the corresponding valves. PI controllers were tuned by IMC design and used to regulate the temperatures. By comparing the outcomes, it´s evident that Simplified Decoupling is the best to reduce the effect of the disturbance by coupling.